Pemanfaatan Vlog Sebagai Komunikasi Interpersonal (Studi Deskriptif Kualitatif Album Ke-7 Endank Soekamti â€œSoekamti Dayâ€) - Giantika, Gan Gan (Universitas Bina Sarana Informatika, 2018)
Increased Internet usage makes artists use the internet as a media campaign and maintain its existence in the community, the medium that is in great demand by famous people is a vlog on youtube , many artists use this media as a promotional tool and the artist's daily information to fulfill information for his fans. One of them who use is indie band Endank Soekamti. The band's group utilized vlogs as a means of promoting their new album. The purpose of this research is to know the process of utilization of vlog as interpersonal communication medium in 7 Kean Soekamti's